2014
DOI: 10.5713/ajas.2013.13852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin C or E on the Pro-inflammatory Cytokines, Heat Shock Protein 70 and Antioxidant Status in Broiler Chicks under Summer Conditions

Abstract: The present study was carried out to investigate the effects of dietary antioxidants on pro-inflammatory cytokines, heat shock protein (HSP) and antioxidant status in broiler chicks under summer conditions. A total of 162, 3-d-old broiler chicks were randomly assigned to a basal diet (CON) and the basal diet supplemented with vitamin C (200 mg/kg diet, VCD) or vitamin E (100 mg/kg, VED) until 35 day of age. All birds were exposed to summer diurnal heat stress at average daily fluctuations of temperature betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 37 publications
(60 reference statements)
13
72
0
6
Order By: Relevance
“…The probable reason for such reports might be due to the fact that rearing broiler chickens for 5-6 weeks may not be long enough for the ascorbic acid to have an effect on muscle metabolism, which could also be the reason for present findings. Jang et al, (2014) reported that dietary supplementation with vitamin C subjected to summer HS in broilers markedly decreased (TBA value) lipid peroxidation in liver compared with the control group, is in agreement to our findings. In the present study, dietary vitamin C significantly decreased hepatic lipid peroxidation.…”
Section: Resultssupporting
confidence: 83%
“…The probable reason for such reports might be due to the fact that rearing broiler chickens for 5-6 weeks may not be long enough for the ascorbic acid to have an effect on muscle metabolism, which could also be the reason for present findings. Jang et al, (2014) reported that dietary supplementation with vitamin C subjected to summer HS in broilers markedly decreased (TBA value) lipid peroxidation in liver compared with the control group, is in agreement to our findings. In the present study, dietary vitamin C significantly decreased hepatic lipid peroxidation.…”
Section: Resultssupporting
confidence: 83%
“…As a consequence, less toxin will be produced and liver will have less work in detoxifying these toxin (Mehr et al, 2007). In terms of the antioxidant property of the fungus, it might have a minimal effect on the liver weight, as Jang et al (2014) reported no effect of antioxidants (vitamins C and E) on the relative weight of liver in broiler chicks. Eventually, the lower liver weight in the present study may confirm that the toxicological effect of urea used as a nitrogen source in the fermentation process did not appear in broiler chicks (Khempaka et al, 2014;Sugiharto et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…그러 나 닭에서 사육 밀도 증가에 따른 동물 복지에 관련된 다양 한 지표들을 조사하였지만, 많은 요인들의 상호작용 및 복 합성으로 이들 지표들의 일관성은 높지 않는 것으로 알려져 있다 (Thaxton et al, 2006). 최근에는 닭에서 사육 밀도, 추위, 고온 등과 같은 외부 스트레스 요인이 친염증 사이토카인 및 항산화 방어력에 영향을 미치는 연구 결과가 발표되었다 (Hangalapura et al, 2006;Jang et al, 2014;Kaiser et al, 2012;Kang et al, 2011). 특히 스트레스에 따른 corticosterone 수준의 증가와 물리적 스트레스 요인이 면역 작용과 직접적 인 연관성이 있다는 연구 결과가 발표되면서 염증 관련 사이 토카인이 스트레스 평가 지표로서 주목 받고 있다 (Hangalapura et al, 2006;Shini et al, 2010).…”
Section: 환경 요인 중 사육 밀도는 육계의 생산성 및 동물 복지와 밀접한 관계가 있는 것으로 고밀도 사육 시 개체의unclassified